An Amplified Description and Conservation Status of a Little Known Endemic: Primula jigmediana W.W. SM. (Family: Primulaceae) - Bawri, A.; Gajurel, P. R.; Khan, M. L. (Journal of the Bombay Natural History Society (JBNHS), 2018)
No Abstract.